Role Playe Method for Numeracy Ability of Students with Intellectual Disability - Galoh Rahmawati Arifatul Nurul Hikmah; Sudarsini Sudarsini; Asim Asim (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
Intellectual disability children who have the below intelligence average hamper their academic intelligence such as numeracy learning especially adding and subtracting. Children with intellectual disability in SLB experience difficulty to do adding and subtracting operation. The role playe method require the students to be active in learning. The purpose of this study is to describe the ability of addition and subtraction of the intellectual disability students before and after using the role playe method. The research is Pre-Experimental Design with One Group Pre-test Post-test Form. The instruments are written and oral test for pre-test and post-test. The analysis technique used is Wilcoxon Test with manual calculation.